Made to Matter : White Fathers, Stolen Generations. - Probyn-Rapsey, Fiona. (Sydney University Press, 2013)
This book analyses the stories of white fathers, men who were positioned as key players in the plans to assimilate Aboriginal people by 'breeding out the colour' and attempts to put textual flesh on the bodies of these white fathers, and in doing so, builds on and complicates the view of white fathers in this history, and the histories of whiteness to which they are biopolitically related.